Workplace Sexual Harassment: Legislative Comparison in Mainland of China, Macao and the US - Li, Zhuotong (Transactions on Social Science, Education and Humanities Research, 2025)
Workplace sexual harassment is a critical issue nowadays, with significant variations in legal frameworks across different jurisdictions, including Mainland of China, Macao, and the US. However, existing studies often focus on single-region analyses, lacking comparative perspectives that could reveal legislative strengths and weaknesses. This lack of legislative comparison leads to certain defects in the laws of these three countries and regions. To address this gap, this study conducts a comparative legal analysis, examining the definitions, preventive measures, and redress mechanisms in the three regions through document analysis and case studies. The results indicate that the US employs a comprehensive, precedent-based system with strong punitive measures, while Mainland of China and Macao rely more on statutory laws but face enforcement challenges due to vague definitions and limited victim protections. Therefore, this research highlights the need for legislative improvements. The findings provide valuable insights for policymakers seeking to refine anti-harassment laws and promote safer workplaces globally.